Money in modern macro models: A review of the arguments - Franz Seitz; Markus A. Schmidt (Ostbayerische Technische Hochschule Amberg-Weiden (OTH), 2014)
This paper provides an overview of the role of money in modern macro models. In particular, we are focussing on New Keynesian and New Monetarist models to investigate their main findings and most significant shortcomings in considering money properly. As a further step, we ask about the role of financial intermediaries in this respect. In dealing with these issues, we distinguish between narrow and broad monetary aggregates. We conclude that for theoretical as well as practical reasons a periodic review of the definition of monetary aggregates is advisable. Despite the criticism brought forward by the recent New Keynesian literature, we argue that keeping an eye on money is important to monetary policy decision-makers in order to safeguard price stability as well as, as a side-benefit, ensure financial market stability. In a nutshell: money still matters. – – Das Papier gibt einen Überblick über die Rolle monetärer Variablen in modernen Makromodellen. Im Mittelpunkt stehen Neukeynesianische und Neumonetaristische Modelle. Ihre Hauptergebnisse werden dargestellt, wobei ein spezieller Fokus darauf gelegt wird, welche Bedeutung monetäre bzw. Liquiditätsvariablen spielen. Darüber hinaus wird untersucht, welche Rolle Finanzintermdediären in dieser Hinsicht zukommt. Insgesamt wird dabei zwischen engen und bereiten Geldmengenaggregaten unterschieden und auch die (theoretische und praktische) Adäquanz traditioneller Geldmengendefinitionen hinterfragt. Wir schlussfolgern, dass es trotz der vielfältigen Kritik an geldmengenorientierten Ansätzen für die Geldpolitik essenziell ist, Geldmengenentwicklungen zu analysieren, soll Preisstabilität und Finanzstabilität erreicht bzw. gesichert werden.
Keywords: E51; E52; E58; 330; money; New Keynesian model; New Monetarist model; financial intermediaries